2015
DOI: 10.1186/s40663-015-0039-2
|View full text |Cite
|
Sign up to set email alerts
|

Holocene variations of wildfire occurrence as a guide for sustainable management of the northeastern Canadian boreal forest

Abstract: Background: Cumulative impacts of wildfires and forest harvesting can cause shifts from closed-crown forest to open woodland in boreal ecosystems. To lower the probability of occurrence of such catastrophic regime shifts, forest logging must decrease when fire frequency increases, so that the combined disturbance rate does not exceed the Holocene maximum. Knowing how climate warming will affect fire regimes is thus crucial to sustainably manage the forest. This study aimed to provide a guide to determine susta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…It is estimated that this period corresponds to a dominance of Picea mariana and A. balsamea forests in the studied landscape, and perhaps in the majority of landscapes belonging to Québec's Clay Belt. The reconstructions of fire history from lake sediments in the western Picea mariana-moss domain also show a general decrease in fire frequency during this period, but with a certain variability among sites [10,28,31,34].…”
Section: Landscapes Dominated By Picea Mariana and Abies Balsamea (Camentioning
confidence: 82%
See 1 more Smart Citation
“…It is estimated that this period corresponds to a dominance of Picea mariana and A. balsamea forests in the studied landscape, and perhaps in the majority of landscapes belonging to Québec's Clay Belt. The reconstructions of fire history from lake sediments in the western Picea mariana-moss domain also show a general decrease in fire frequency during this period, but with a certain variability among sites [10,28,31,34].…”
Section: Landscapes Dominated By Picea Mariana and Abies Balsamea (Camentioning
confidence: 82%
“…1000 BP for some lakes (Profond, Raynald, Richard and Nans; Figure S1) but low for others (Geais, Loutre, Twin, Aurélie). These differences could be associated with the short duration of the Medieval Warm Period, which caused a varied fire pattern in the western portion of Picea mariana-moss domain [28]. Differences in physical features probably do not explain this variability because lakes with high and low fire frequency are located both in peatlands (Profond, Raynald, Geais, Loutre) and till environments (Richard, Nans, Twin, Aurélie).…”
Section: Increase Of Early Successional Species (Ca 2100 To Ca 800 Bp)mentioning
confidence: 99%
“…Radiocarbon dates [calibrated at 2 sigma ranges based on the Intcal13.14C data set (Reimer et al ., )] and chronology have already been published by El‐Guellab et al . (). A summary is presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Annual and August precipitation averages are 961 and 105 mm, respectively (Environnement Canada, 2017). Further details about the study site characteristics can be found in El-Guellab et al (2015).…”
Section: Study Area and Sitementioning
confidence: 99%
“…The last 2000 years included both the warm Medieval Climate Anomaly (MCA; approximately 1000 ± 300 cal a BP), and the cold and wet Little Ice Age (LIA; approximately 300 ± 100 cal a BP) (Kerwin et al, 2004;Booth et al, 2006). The MCA was a rapid, intense climate change recorded by several studies in eastern Canada (Bajolle et al, 2018), in Greenland (Kobashi et al, 2010), and more largely in the Northern Hemisphere (PAGES 2k Consortium, 2013;Ljungqvist, 2010), and suspected to have increased the fire activity for a short duration in some boreal forest regions (Kelly et al, 2013;El-Guellab et al, 2015). These more frequent fires were not recorded in our fire reconstructions, but were observed at other sites in north-eastern Canada (Ali et al, 2012;El-Guellab et al, 2015;Remy et al, 2017).…”
Section: Drivers Of Vegetation Trajectoriesmentioning
confidence: 99%